El costo de producción y su incidencia en la rentabilidad de la empresa Orecao S.A, cantón Quevedo, año 2012 - Falcón Albuja, Grimanesa Del Rocío (2015)
This research was conducted at the company Orecao SA, located in the city of Quevedo, at kilometer first of the way to Valencia. The research was conducted with the aim of analyzing the production costs and their impact on the profitability of an agricultural enterprise. In this case it is the agricultural production of cacao, in which the system cost control plays an important role for monitoring your production, as well as the costs of materials and supplies needed in the production of cocoa.To identify the components of the cost of cocoa production activity was necessary to know the agricultural process from planting, through the maintenance of crops by various agricultural works to finish at harvest and finally the marketing of the cocoa bean. Without this knowledge would have been very difficult to understand the accounting implications of the production process.To meet the objectives of research include consulting secondary sources, as well as collecting information directly through observation and interviews with the General Manager, who is also in charge of production, and the Count the company.The research results confirm the need to implement an accounting system attached to the definitions set out in the International Accounting Standard No. 41, which contains the accounting standards of biological assets.Thus the importance of defining parameters to measure performance, identifying improvements and corrective measures that directly affect economic benefits to the company is also evidence.To study all the hypotheses were tested, which emphasize the importance of a proper analysis of production costs to make good decisions that positively affect the profitability of the company.